TPACK and Digital Science Literacy: Correlational Insights from Preservice Science Teachers - Muhammad Ikhsan Sukaria; Nursalim (Jurusan Teknik Informatika dan Komputer, 2025)
Integrating technology into primary science education requires preservice teachers to develop robust Technological Pedagogical Content Knowledge (TPACK) alongside Digital Science Literacy (DSL). This study tests the correlation between TPACK and DSL among preservice primary teachers engaged in designing digitally enhanced science lessons. A cross-sectional correlational design was used with validated instruments for TPACK and DSL (Cronbach's α = 0.95 and 0.92). Descriptive statistics and Pearson correlation were computed with 95% confidence intervals. Results indicate a medium, positive association (r = 0.41, p < .001), strongest for advanced indicators—data interpretation and variable identification/control—compared with foundational indicators such as observation and classification. Findings suggest that pedagogically grounded technology integration aligns with critical evaluation and use of scientific information in digital environments. Programs should prioritize inquiry- and project-based tasks that require designing technology-enhanced lessons, analyzing empirical data (e.g., simulations/virtual experiments), and constructing evidence-based arguments. The study contributes empirical support for linking TPACK development with DSL outcomes in preservice science education and offers actionable guidance for curriculum and assessment design.